Not your Mama's beading : - Shoup, Kate (Wiley, 2006)
This beading book offers projects that are chic, unique, and absolutely wearable. With more than thirty super-cool designs, it covers essential tools and materials, must-know beading techniques, and ideas for personalizing every project. You’ll whip up designs with pizzazz to adorn your apartment, your friends, or yourself! With a sassy attitude, hip projects, and color photos, this will bring out your inner diva.